A case of gossypiboma mimicking intrahepatic cholangiocarcinoma - Ojha, S (Ann R Coll Surg Engl, 2014)
INTRODUCTION: A gossypiboma refers to a cotton-based foreign body left inadvertently in the human body following a surgical procedure. Although a rare event, they tend to be found in the abdomen but few are known to be intrahepatic. CASE HISTORY: We report the case of a 44 year-old man who presented with recurrent episodes of jaundice and cholangitis, on a background of a right hepatectomy for hydatid cyst excision 20 years previously. This case was discussed at our hepatobiliary multidisciplinary team meetings on several occasions and a presumed diagnosis of intrahepatic cholangiocarcinoma was made. Biopsies of the mass had purely shown inflammation and remained inconclusive. It was decided that the patient should undergo a complete extended right hepatectomy with resection and reconstruction of the left branch of the portal vein. On attempting to obtain intraoperative frozen section specimens prior to resection, open excision revealed two large swabs encased in a calcified cavity. Removal of the swabs resulted in resolution of the mass and obstructive symptoms. CONCLUSIONS: Gossypiboma should be a rare differential diagnosis in all patients following a laparotomy presenting with obstructive symptoms, particularly in countries where strict surgical protocols may not be in place. This case also highlights the need to perform an intraoperative biopsy in any uncertain case of a liver lesion as we have shown that an extensive operation with its increased morbidity can occasionally be avoided.